DIGITAL LITERACY FOR LIBRARIANS IN THE ERA SOCIETY 5.0: OPPORTUNITIES AND CHALLENGES (International Conference on Social and Islamic Studies, 2022)
In the sophisticated technology ere, digitazation, virtual and online things become normality following current and future expectations, such as the slogan “world in our grip”. As information management institution, library is no longer focused on building physical and conventional services but must develop itself flow the times. Librarians play an active role in making innovations and services for users. The purpose of this study is to determine the ability of digital literacy in the era of society 5.0 of librarians. This study is a qualitative research by using literature study approach. Therefore, the data were gathered through previous studies conducted by researchers or academicians. In reality, the context of digital literacy for librarians who have long been part of the library, but the digital phenomenon that is basically related to digital media users is still not optimal in its utilization in the society 5.0 era.